Remote Sensing Implementation into Geoinformation Support for Managerial Decision in Arctic - Valery M. ABRAMOV; Vyacheslav G. BURLOV; Evgeniy A. BAIKOV; Vladimir A. BOLSHAKOV; Eugene P. ISTOMIN; Valery L. MIKHEEV; Oleg I. SHEVCHUK; Mikhail B. SHILIN; Igor A. SIKAREV; Yaroslav A. PETROV (Communications of International Proceedings, 2021)
Article considered remote sensing implementation for managerial decision support while large arctic projects under conditions of climate change and Covid-19 within Industry 4.0 period The research uses Foresight technologies, web-technologies and the methods of data bases constructing. As research result, authors recommend to implement the using Earth remote sensing data in geoinformation support of managerial decision processes to increase the efficiency and reliability of such projects realization. As implementation tools, it is proposed the using of aggregate modular expert systems with geoinformation digital online platforms, as modules, which integrate heterogeneous hardware and software resources with the use of web-technologies in distributed networks. As study results, some examples of geoinformation support with remote sensing data for managerial decision in Arctic are demonstrated. The presented research results have significant scientific novelty and can be useful for state environmental control bodies, public environmental organizations of the civil sector and private investors. While research, platform https://www.researchgate.net/profile/Valery_Abramov2/ was used for preliminary discussion and data exchange.
Keywords: Remote Sensing; Geoinformation Support; Managerial Decision; Arctic